PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI) - Mardani, Ronny Malavia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
The objective of this study is to analyze the influence of Intellectual Capital to Corporate Finance Performance. Based on the result of this study, show that : a) There is a positive influence of Intellectual capital (VACA, VAHU, and STVA) to the company's financial performance (Return on Equity, Return on Total Assets, Asset Turn Over, and Growth Revenue).; b) There is a positive influence of Intellectual capital (Vaca, VAHU, and STVA) to the future of company's financial performance, and c) There is a positive influence of average growth of the Intellectual Capital to the future company's financial performance.. Â